Facile method for producing silicon containing porous carbon nanofibres from amphiphilic copolymers and controlling precursor fibre morphology - Human, Chantelle (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.